Intraoperative Frozen Section Assessment of Myometrial Invasion and Histology of Endometrial Cancer Using the Revised FIGO Staging System. Issue 7 (1st October 2011) - Ugaki, Hiromi; Kimura, Toshihiro; Miyatake, Takashi; Ueda, Yutaka; Yoshino, Kiyoshi; Matsuzaki, Shinya; Fujita, Masami; Kimura, Tadashi; Morii, Eiichi; Enomoto, Takayuki
Abstract : Objectives: The objective of this study was to assess the value of intraoperative frozen section (IFS) diagnosis for myometrial invasion and histology of endometrial cancer using the revised International Federation of Gynecology and Obstetrics (FIGO) staging system. Methods: The medical records of 303 patients with endometrial cancer who underwent surgery with intraoperative diagnosis at the Osaka University Hospital between January 1999 and December 2008 were reviewed. Intraoperative frozen section diagnosis was retrospectively analyzed for the accuracy rates of myometrial invasion and histology compared with the final diagnosis and with preoperative prediction by magnetic resonance imaging (MRI) and endometrial curettage. Results: When using the previous FIGO staging system, the accuracy rate of IFS for the diagnosis of myometrial invasion was 77%, whereas the accuracy rate of preoperative prediction by MRI was 54%. However, using the newly revised FIGO staging system for myometrial invasion, the accuracy rate of IFS was 87% and the preoperative prediction by MRI was 82%. The accuracy rate of IFS for the diagnosis of histology was 71%, whereas the accuracy rate of preoperative prediction by endometrial curettage was 68%. Conclusion: Although under the previous FIGO staging system IFS diagnosis was significantly more accurate than preoperative prediction by MRI, when using the newly revised FIGO staging system, there are no significant differences between the values of preoperative and intraoperative diagnoses. The accuracy of IFS, however, trends to be slightly better than the preoperative procedures of MRI and endometrial surface biopsy. Thus, IFS diagnosis is still useful for directing primary operative management.